Reasoning of the selection of technological parameters for the extraction of sumac - Bandura (Kuzmyk), Uliana; Yushchenko (Gonchar), Natalia; Osmak (Fedchenko), Tetiana; Mykhalevych, Artur (My University, 2020)
In order to intensify the extraction process, the possibility of using a rotary-pulse apparatus was investigated. The use of rotary-pulse extractors makes it possible to intensify the process of eliciting extractive substances of plant raw materials in comparison with traditional methods, to improve the microbiological parameters of the obtained extracts due to the tightness of the circuit and to ensure the energy efficiency of the process. It was found that with increasing temperature, the mass fraction of extractives increased, while the duration of the process at the selected temperature was of great importance. The duration of the extraction at a temperature of 20 ° C for 10 min, gave the same yield of extractives as heating the system "raw materials/solvents" to a temperature of 80 °C without endurance.
Keywords: extraction; кафедра технології молока і молочних продуктів; екстракція; екстрактор роторно-імпульсний